Digital oscillation rails: developing physics learning media to determine the acceleration value of earth's gravity. (June 2020) - Diani, R; Satiarti, R B; Lestari, N; Haka, N B; Reftyawati, D; Padilah, A; Komikesari, H
Abstract: This research aims to develop a feasible learning media for high school physics learning on mathematical swing material, especially in determining the value of Earth's gravitational acceleration. The learning media developed is a visual aid in the form of digital oscillation rails. This is a research and development research using the ADDIE model (analysis, design, development, implementation, and evaluation). The results of validation, teacher responses, and trials to students indicate that the developed digital oscillation rails are in the highly feasible category. Digital oscillation rails made of two oscillations tracks. The average values of gravitational acceleration obtained based on three experiments are 9.05 m / s 2 for a track with 25 cm radius and 9.97 m / s 2 for a track with 15 cm radius.